2012
DOI: 10.1089/aid.2011.0106
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance and Coreceptor Usage in HIV Type 1 Subtype C-Infected Children Initiating or Failing Highly Active Antiretroviral Therapy in South Africa

Abstract: HIV-1 drug resistance monitoring in resource-poor settings is crucial due to limited drug alternatives. Recent reports of the increased prevalence of CXCR4 usage in subtype C infections may have implications for CCR5 antagonists in therapy. We investigated the prevalence of drug resistance mutations and CXCR4 coreceptor utilization of viruses from HIV-1 subtype C-infected children. Fifty-one children with virological failure during highly active antiretroviral therapy (HAART) and 43 HAART-naive children were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…A high prevalence of drug-resistance mutation occurs in untreated, HIV infected infants, reaching 32% in Senegal [97] and 85.4% in South Africa [98], although prevalence was much lower at 4.9% in Cameroon [99]. Longer exposure to failing regimens increased the rate of TAM, which can compromise subsequent second-line treatments [97].…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 99%
“…A high prevalence of drug-resistance mutation occurs in untreated, HIV infected infants, reaching 32% in Senegal [97] and 85.4% in South Africa [98], although prevalence was much lower at 4.9% in Cameroon [99]. Longer exposure to failing regimens increased the rate of TAM, which can compromise subsequent second-line treatments [97].…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 99%
“…Previously, X4-tropic strains have been reported to be very rare in HIV-1C infection, even in the later stage of disease [911]. Some recent studies from South Africa and India also showed predominance of R5 strains in treatment naïve as well as experienced HIV-1C infected patients [12], although a South African study reported predominance of X4 strains in treatment experienced children [13]. More recently, a higher incidence of X4-tropic HIV-1C were described in patients with advanced immunodeficiency from South Africa, India and Botswana, respectively [1417].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Since the frequency of coreceptor switching is influenced by both HIV-1 subtype 28,29 and host CCR5 genotype, [30][31][32] both viral and host factors must contribute. Coreceptor switching is less frequent in subtype C HIV-1 infection 29,33 but the frequency increases [34][35][36] following antiretroviral therapy (ART), as it does in subtype B infection. 17,37 Subjects heterozygous for the CCR5 D32 mutation tend to have lower viral loads 38,39 but earlier emergence of R5X4 or X4 variants, 32 suggesting that entry fitness and selective pressure to use CXCR4 are influenced by CCR5 density.…”
Section: Introductionmentioning
confidence: 99%